2008
DOI: 10.1194/jlr.m700437-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin increases human serum levels of proprotein convertase subtilisin/kexin type 9

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) has gained attention as a key regulator of serum low density lipoprotein cholesterol (LDL-C) levels. This novel protease causes the degradation of hepatic low density lipoprotein receptors. In humans, gain-of-function mutations in PCSK9 cause a form of familial hypercholesterolemia, whereas loss-of-function mutations result in significantly decreased LDL-C levels and cardiovascular risk. Previous studies have demonstrated that statins upregulate PCSK9 mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
205
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(233 citation statements)
references
References 25 publications
24
205
0
3
Order By: Relevance
“…Moreover, inhibition of PCSK9 expression resulted in a two-fold increase in hepatic LDL receptor levels [Graham et al, 2007]. These experiments confirmed that inhibition of PCSK9 activity should enhance statin hypocholesterolemic effect by increasing LDL receptor number [Rashid et al, 2005;Careskey et al, 2008]. Finally, the low plasma LDL-C levels and the reduction of CHD displayed in PCSK9 loss-of-function mutation carriers, which seem furthermore healthy, indicate that the inhibition of PCSK9 should be an effective target in the treatment of hypercholesterolemia with no known adverse side effects.…”
Section: Future Prospectssupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, inhibition of PCSK9 expression resulted in a two-fold increase in hepatic LDL receptor levels [Graham et al, 2007]. These experiments confirmed that inhibition of PCSK9 activity should enhance statin hypocholesterolemic effect by increasing LDL receptor number [Rashid et al, 2005;Careskey et al, 2008]. Finally, the low plasma LDL-C levels and the reduction of CHD displayed in PCSK9 loss-of-function mutation carriers, which seem furthermore healthy, indicate that the inhibition of PCSK9 should be an effective target in the treatment of hypercholesterolemia with no known adverse side effects.…”
Section: Future Prospectssupporting
confidence: 64%
“…Serum PCSK9 measured by ELISA seems directly correlated with serum LDL-C and total cholesterol [Alborn et al, 2007]. Atorvastatin (40 mg/ day) increases human serum levels of PCSK9 by 34% compared with baseline and placebo [Careskey et al, 2008], while fenofibrate (200 mg/day) decreased plasma PCSK9 concentrations by 8.5% in diabetic patients [Lambert et al, 2008]. However, a standardized method, with specific antibodies, is still needed to compare the levels of PCSK9 measured in different studies.…”
Section: Diagnostic Relevancementioning
confidence: 99%
“…Statins have been known to increase the nuclear translocation of sterol-regulatory element binding protein-2 (SREBP-2), which activates not only the LDLR but also PCSK9 gene expression [4][5][6]. Subsequently, statins increases serum PCSK9 levels [5][6][7][8] and this increment may attenuate the LDL-C lowering effect of statins. It may in a part explain the rule of 6% for statins, which indicates that each doubling of the statin dose results in only about a 6% further decrease in LDL-C.…”
Section: Introductionmentioning
confidence: 99%
“…Statins increase PCSK9 levels [16], which probably accounts, in large part, for the limits in the incremental effectiveness of statins during up-titration [17]. Because of the intersecting mechanisms of statins enhancing LDL receptor (LDL-R) activity and lowering LDL-C, but also increasing PCSK9 expression (which can in turn destroy LDL-Rs and reduce LDL-C lowering effects), the combination of statins and PCSK9 inhibitors could theoretically have positive complementary and additive effects on LDL-C reduction [18].…”
Section: Discussionmentioning
confidence: 99%